2022
DOI: 10.35371/aoem.2022.34.e27
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep quality and type of shift work in Korean firefighters

Abstract: Background Shift work that interferes with normal sleep patterns, is known to be a cause of sleep disturbance and has been studied through various occupational groups. However, it is not known which shift type is better for sleep health. Methods This study included 568 firefighters. Sleep quality was evaluated using Pittsburgh Sleep Quality Index. Sleep quality was categorized into 2 groups; good quality (≤ 5 points) and poor quality (≥ 6 points). Demographic variables,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The present study did not find any correlations with the exercise variable. These results highlight the need for more investigation into such a field of interest, especially considering that other research indicates that exercise can cause an increment in blood levels as an adaptation response to training [ 42 , 106 , 107 ]. Such variations and mechanisms are only partially understood [ 108 , 109 ].…”
Section: Discussionmentioning
confidence: 84%
“…The present study did not find any correlations with the exercise variable. These results highlight the need for more investigation into such a field of interest, especially considering that other research indicates that exercise can cause an increment in blood levels as an adaptation response to training [ 42 , 106 , 107 ]. Such variations and mechanisms are only partially understood [ 108 , 109 ].…”
Section: Discussionmentioning
confidence: 84%
“…Sleep problems are common in shift workers, such as healthcare professionals (39.2%) ( 19 ), night shift autoworkers (56.2%) ( 20 ), and firefighters (59.3%) ( 21 ), and their prevalence is relatively higher than the general population (16.6–35.9%) ( 22 24 ). In this study, we observed a higher prevalence of sleep disorders in professional airline pilots, mirroring the result obtained from national commercial pilots in Saudi Arabia ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%